Pengaruh Ekonomi Pengetahuan dan Tingkat Kemiskinan di Indonesia - Nefo Indra Nizar; Ahmad Nazir; Achmad Nur Sholeh (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2026)
This study aims to analyze the influence of the knowledge economy on poverty levels in Indonesia. The knowledge economy is proxied through education, technology, innovation, and institutions, which are believed to play a significant role in improving the quality of human resources and public welfare. This study uses a quantitative approach with panel data across 33 provinces in Indonesia. The analysis method used is the Least Square Dummy Variable (LSDV) to determine the influence of independent variables on poverty levels in Indonesia. The results show that education, technology, and innovation have a negative and significant influence on poverty levels. Meanwhile, institutions are not included in this study. The findings of this study indicate that improving the quality of human resources and strengthening the knowledge-based economy can be important instruments in poverty alleviation in Indonesia. Therefore, the government needs to increase investment in the education sector, digital technology, research and innovation, and strengthen development institutions for more inclusive and sustainable economic growth.